PENGEMBANGAN MODUL AJAR BERBASIS MODEL RAYISAH PADA LEMBAGA KURSUS DAN PELATIHAN - Sri Rahayu; Anim Anim (EDUTECH, 2022)
AbstractThis study aims to: (1) produce teaching modules based on the Rayisah learning model that are suitable for use in learning English and (2) to determine the effectiveness, validity, and practicality of the teaching module based on the Rayisah learning model. This type of research is research and development that uses the RD model from Borg and Gall combined with the instructional design model from Dick and Carey. This research method has two stages, namelyIn the phase of developing and trial, the product must pass some validations and trial processes. The result shows that: (1) the assessment of instructional material experts is in the criteria of “very good” (82,94%), (2) the assessment of instructional design experts is in the criteria of “very good” (81,58%), (3) the assessment of instructional model expert is in the criteria of “very good” (94,42%), (4) the assessment of media experts is in the criteria of “very good” (85%), (5) the assessment of individual trial is in the criteria of “very good” (81,03%), (6) the assessment of small group trial is in the criteria of “very good” (90,09%), and (7) the assessment of field trial is in the criteria of “very good” too (92,08%).In the phase of testing the product’s effectiveness, the methode used is quasi experiment. 20 students are in the experimental class which were taught with a life skills based instructional model and 20 students are in the control class which were taught with a conventional one. The result of hypothesis testing indicates that there is a significant difference between the students’ learning outcome in the experimental class and the students’ learning outcome in the control class. This result is concluded based on the post test data processing in which tcount ttable (3.34 1.68) at the significance level of α = 0.05. Therefor, the life skills based instructional model is proper and effective used in learning English at training and course institute.